The Onset of Lactation After an Uncomplicated Cesarean Delivery: A Randomized Controlled Study Between Early Post Operative Feeding and Conventional Feeding - Nalinee Deawvatanavivat (The Royal Thai College of Obstetricians and Gynaecologists, 2010)
Objective:To compare the onset of lactation after an uncomplicated cesarean delivery between early feeding and conventional feeding.Material and methods: One hundred and forty - four uncomplicated post cesarean mothers were enrolled. Seventy-two of them were randomized into each group. The study group had early feeding while the control group started feeding with the conventional method. Demographic data were collected. The onset of lactation were interviewed, confirmed and recorded from both groups. The normal distributed data were described in mean, standard deviation and compared by independent t-test. The Chi-square test and two-tailed t-test were used to analyze the categorical and continuous data. Statistical significance was considered when p value < 0.05.Result:There was no difference in demographic data between the study and control group. The onset of lactation in the study and control group were 43.55+13.58 hrs and 56.40+11.23 hrs, respectively. The onset of lactation in the study group was significantly lesser than the control group (P < 0.001).Conclusion: The early feeding in uncomplicated post caesarean mothers had earlier onset of lactation than the conventional feeding.